Bedtime for sweet creatures eaudiobook - Grimes, Nikki (Recorded Books Inc., 2020)
A sweet bedtime story from the award-winning author Nikki Grimes about a mother, her little boy, and their imagination-fueled and animal filled journey to get to sleep. It's bedtime. But Mommy's little one is not sleepy. He growls like a bear, he questions like an owl, he tosses his mane like a lion. He hunts for water like a sly wolf, and hides like a snake. Mommy needs to wrangle her sweet creature for sleep in this endearing and imagination-fueled journey to bedtime, from Children's Literature Legacy Award–winning author Nikki Grimes and acclaimed illustrator Elizabeth Zunon.